Indoor air quality in selected school buildings in the Central Sector of Athens at the Attica’s Region and potential Health Risks - Bikaki, Maria Anna; Dounias, Georgios; Farantos, Georgios; Cavoura, Olga; Damikouka, Ioanna; Evrenoglou, Lefkothea (European Scientific Journal, ESJ, 2024)
Aims and scope: Indoor air pollution is considered as an important environmental risk factor for health. Indoor air quality in schools is very important, as students and teachers spend most of their day (30%) indoors and consequently are more exposed to indoor pollution than outdoor air pollution. The present study has the aim to investigate the indoor air quality (IAQ) in school buildings in the Central Sector of Athens at the Attica’s Region and record physical parameters and concentration levels of indoor air pollutants that are associated with comfort, health and safety conditions inside the classrooms. Methods: The indoor air quality research was conducted in forty-seven (47) classrooms in a total of twenty-six (26) school buildings in the Central Sector of Athens at the Attica’s Region, during the period from March 2022 to May 2023. The air pollutants Carbon dioxide (CO2), Carbon monoxide (CO), Volatile Organic Compounds (VOC’s), Nitrogen dioxide (NO2), Particulate matters PM (PM10, PM2.5) and physical parameters such as temperature (T) and relative humidity (RH) were monitored by the series 500 Portable Air Quality Monitor AeroQual, during (1) teaching hour per day in each classroom. During the samplings some windows and doors were opened, due to measures and recommendations for health and safety for students and teachers against COVID-19. Findings: The overall mean concentrations of the main parameters recorded inside the schools were 0,136 ppm CO, 823,38 ppm CO2, 12,07 ppm VOC’S, 0,006 ppm NO2, 38,1 μg/m3 PM10 and 15,4 μg/m3 PM2.5. The mean recorder temperature was 24,52 oC, and relative humidity was 45,78%. In this study a total number of twenty- two (22) classrooms (46,8%) of schools at the Attica’s Region had no comfort temperatures for students. In all cases indoor CO concentrations were below the 50 ppm, guideline set by WHO. Eight (8) of the forty-seven classrooms in the Region of Attica (17%) had a CO2 concentration more than 1000ppm. VOC’s exceeded the limit value of 0,8ppm indoors in all schools (100%). There was statistically difference for CO, CO2, ΝΟ2 (p<0,001), for VOC’s (p=0,004) and for PM10 (p=0,028) between indoor and ambient air. Conclusion: The indoor air quality of the classrooms was influenced by the outdoor air, the location of school, the number of windows that were opened during the lesson, the number of students inside the classroom, the activities, furnishing and school equipment. No comfort conditions in classrooms and exceeded limits of indoor air pollutants can lead to diminished IAQ and thereby harmful effects on students. A well airing of the classrooms during the lessons and breaks is necessary for a better air quality. Ventilation is one of the most important factors affecting indoor air quality, diluting the exposure agents originating from indoors.